TECHNIQUES OF ROCKFALL INVENTORY IN EARTHQUAKE PRONE ROCK SLOPES - Zygouri, V.; Koukouvelas, I. (Bulletin of the Geological Society of Greece, 2016)
A relevant hazard in mountainous regions is the steep rock slopes concentrating rock falls. Although rock falls are characterized by smaller rock volumes compared to other landslide types, can also provoke severe damage to buildings, infrastructures and human life due to their sudden and highly fast movement. The key to understand the processes that result in rock fall onset is an integrated study of the major causing parameters that affect slope stability. A rock slope may be subjected to many forms of triggering factors including tectonic, geomorphic, seismic, climatic or even human induced damages. This contribution provides an overview of the previous and current research related to rock falls and uses case studies of North Peloponnese in order to prove the usefulness of these methods in the Greek territory. Collecting data and production of thematic maps by means of field and remote sensing investigations can yield far more updated results incorporated in hazard assessment techniques and protection measures.